Integrating an open-source course management system (Moodle) into the teaching of a first-year medical physiology course: A case study - Seluakumaran, K.; Jusof, F.F.; Ismail, R.; Husain, R. (American Physiological Society, 2011)
Seluakumaran K, Jusof FF, Ismail R, Husain R. Integrating an open-source course management system (Moodle) into the teaching of a first-year medical physiology course: a case study. Adv Physiol Educ 35: 369-377, 2011; doi:10.1152/advan.00008.2011.-Educators in medical schools around the world are presently experimenting with innovative ways of using web-based learning to supplement the existing teaching and learning process. We have recently used a popular open-source course management system (CMS) called the modular object-oriented dynamic learning environment (Moodle) to construct an online site (DPhysiol) to facilitate our face-to-face teaching of physiology to a group of first-year students in the Bachelor of Medicine and Bachelor of Surgery program. The integration of the Moodle site into our teaching was assessed using online log activity, student examination marks, and feedback from students. The freely available Moodle platform was simple to use, helped to effectively deliver course materials, and has features that allowed cooperative learning. Students used the CMS throughout their academic year and commented favorably regarding its use as a complement to the face-to-face classroom sessions. The group of students who used the CMS obtained significantly higher scores in the final examination compared with the previous class that did not use the CMS. In addition, there was a significant correlation between student participation and performance in online quizzes and their final examination marks. However, students' overall online usage of the CMS did not correlate with their examination marks. We recommend Moodle as a useful tool for physiology educators who are interested in integrating web-based learning into their existing teaching curriculum.